The effect of stigma reduction initiatives on HIV testing rates among college students in region XI: The mediating role of safer sex practices - Lynard Bobby L. Asirit (International Research Journal of Science, Technology, Education, and Management)
This study investigates HIV-related behaviors, knowledge, attitudes, and practices (KAP) among college students in Region XI. It aims to understand the impact of stigma reduction initiatives on HIV testing rates, assess safer sex practices, examine KAP regarding HIV/AIDS, and investigate the mediating role of safer sex practices. Stigma reduction initiatives were found to foster supportive environments but did not significantly increase HIV testing rates. Instead, age, gender, and type of educational institution were more influential determinants of testing behavior. Demographic factors had limited impact on the choice of abstinence as a safer sex practice, emphasizing unaccounted variables in decision-making. While participants exhibited good knowledge and positive attitudes toward HIV/AIDS, variability within the sample highlighted the need for tailored interventions. Sociodemographic factors had minimal influence on KAP. The promotion of safer sex practices did not serve as a mediating factor in the relationship between efforts to reduce stigma and the rates of HIV testing. Neither stigma reduction initiatives nor safer sex practices directly impacted testing rates, suggesting the presence of unexplored variables. The study underscores the complexity of HIV-related behaviors among college students. Tailored interventions that consider demographic diversity and go beyond stigma reduction are essential. Comprehensive sexual education programs should address diverse determinants of safer sex practices. Inclusive education on HIV/AIDS is crucial, and further research is needed to explore nuanced factors influencing HIV testing and safer sex practices.